2011
DOI: 10.1353/trn.2011.0047
|View full text |Cite
|
Sign up to set email alerts
|

Minding the gap: attitudes toward affirmative action in South Africa

Abstract: Since its introduction, affirmative action has become an increasingly controversial policy to address labour market inequalities in South Africa. Yet, in spite of this public debate, nationally representative, empirical research on patterns of opposition to and support for the redress policy remains relatively circumscribed. In this article, attitudinal data collected over the past decade is employed to examine the factors that influence these perceptions, and the extent to which they have been changing. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
5
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…They explained the findings in terms of instrumental self‐interest of the Black participants, who accepted as fair the outcomes that would benefit them, and of White respondents, who rejected outcomes that were seen as disadvantageous to them. The survey data reported by Roberts et al () tends to support this interpretation, revealing higher levels of support for affirmative action policies among groups “with the most to gain from policy implementation” (p. 12). This includes Black respondents over White respondents and the unemployed over the employed.…”
Section: The P‐i Gap In Post‐apartheid South Africamentioning
confidence: 95%
See 3 more Smart Citations
“…They explained the findings in terms of instrumental self‐interest of the Black participants, who accepted as fair the outcomes that would benefit them, and of White respondents, who rejected outcomes that were seen as disadvantageous to them. The survey data reported by Roberts et al () tends to support this interpretation, revealing higher levels of support for affirmative action policies among groups “with the most to gain from policy implementation” (p. 12). This includes Black respondents over White respondents and the unemployed over the employed.…”
Section: The P‐i Gap In Post‐apartheid South Africamentioning
confidence: 95%
“…Almost identical results were found in a survey conducted in 2003 at University of Kwa‐Zulu Natal in which respondents were asked: “Do you think that students should go to the same schools of separate schools or are you unsure?” (p. 280). Results of SASAS surveys conducted by the Human Sciences Research Council over the period 2003 to 2009 similarly indicated that the levels of support for the general principle of poverty reduction were high, with 82% of respondents agreeing with the statement “The government should provide a decent stand of living for the unemployed” (Roberts, Weir‐Smith, & Reddy, , p. 6).…”
Section: The P‐i Gap In Post‐apartheid South Africamentioning
confidence: 99%
See 2 more Smart Citations
“… 10. National opinion and attitude surveys in the period 2003–2009 found that on average just under two thirds of South Africans supported preferential hiring and promotion of black South Africans. However, the gulf between ethnic groups or sub-groups is quite substantial, with about three quarters of Africans, slightly more than a quarter of Coloureds and Indians and less than one fifth of Whites supporting such a proposition (Roberts et al, 2011). …”
mentioning
confidence: 99%